Financial Crises and Emerging Market Trade - Thomas, Alun (IMF Staff Position Notes; Staff Position Note ;, 2009)
This chapter discusses various aspects of financial crises and emerging market trade. The current global financial crisis and the sharp reduction in trade flows have raised questions about the extent to which access to capital affects the ability of companies to produce and sell exports and to buy imports. The results presented in this chapter imply that financial conditions play a significant, however, not dominant role in stimulating trade volumes among emerging market countries. Estimates presented in this paper suggest that the combination of zero net private capital flows to emerging markets and a domestic banking crisis could lower import volume growth by between 5 and 6 percent on impact, with a slightly lower effect on export volumes. It is also important to recognize that trade finance is not the only form of credit with implications for trade volumes. Conditions in credit markets more generally, including for working capital and long-term investment financing also have an impact on international trade, including through their impact on industrial production more generally. As such, it is probably sensible for policymakers to support credit flows in general rather than to focus specifically on increasing trade finance.